Hepatitis B & C Viral Markers Status in Icteric Children at a Tertiary Care Hospital - Matin, Abdul; Islam, Md. Rafiqul; Mridha, Md. Al-Amin; Mowla, Md. Golam; Khan, Rita; Islam, Md. Reazul (Journal of Shaheed Suhrawardy Medical College, 2012)
Background: Hepatitis B (HBV) and Hepatitis C virus (HCV) can cause important morbidity and mortality and are major causes of acute and chronic liver disease worldwide. Objectives: This study was an attempt to evaluate the seroprevalence rate of hepatitis B and C in jaundiced children who were admitted at Bangabandhu Sheikh Mujib Medical University. This would be helpful to take measure for the prevention of hepatitis B and hepatitis C infection in paediatric age group. Methodology: A total of 50 admitted jaundiced children of either sex selected randomly were studied during July 2004 to June 2005 in the Department of Paediatrics of Bangabandhu Sheikh Mujib Medical University. Venous blood was tested for HBsAg and anti-HBcAb (IgM) and anti-HCV viral markers by ELISA. Results: The HBsAg test was positive among 24.0 %, Anti-HBcAb (IgM) test positive in 14.0 %. HBsAg was positive in 66.66% of male children and 33.33% of female children. Sero positivity was more in the 10 years age group. Conclusion: This study shows high rate of HBsAg and Anti- HBcAb IgM seropositivity among icteric sick children so, further studies with appropriate design & sample size to be conducted. J Shaheed Suhrawardy Med Coll, 2011;3 (2): 35-37 DOI: http://dx.doi.org/10.3329/jssmc.v3i2.12075